Evaluating person‐centredness for frail older persons in nursing homes before and after implementing a palliative care intervention - Christina Bökberg; Lina Behm; Birgitta Wallerstedt; Gerd Ahlström (Wiley, 2020)
Abstract Aim To evaluate person‐centeredness in nursing homes from the perspective of frail older persons, before and after implementing an educational intervention about palliative care. Design A crossover design. Methods Forty‐four older persons living in nursing homes were interviewed. A convergent mixed‐method was used to analyse data. Results The older persons expressed feelings of unsafety related to shortcomings in staff. These shortcomings implied that the responsibilities of everyday activities and making the residents' existence more bearable were transferred to the next of kin. The dropout rate related to death and not enough energy was considerably high (51%) even though one of the inclusion criteria was to have enough energy to manage a 1‐hr interview. This result supports previous research describing the difficulties in retaining older persons in research and indicated that the dose of the intervention was not sufficient to improve person‐centred care.